The Role of Innovative Value in Formation of the Mental Image of the Organization: An exploratory: Study of the views of a sample of managers in a number of construction organizations in Duhok city - Abbas Al - Mahmoud, Saad F.; Mikho Qelo, Eiveet Sh.; Ramadhan Al-Sharvany, Delman Kh. (Humanities Journal of University of Zakho, 2019)
Organizations have recently faced a number of global changes and developments in the business environment as a result of political, economic, social, technological and legal changes which affect the mental image of the organization. Innovation has become the organizational goal of all organizations that compete fiercely in a world where globalization is intensifying. The mangers look at the innovation not only as a new way of working, but as a real means for organizations to survive and sustain long-term exploration and exploitation of undisputed market areas because competition in crowded markets is not a means of preserving market share of the organization. The formation of a good mental image has become a fundamental goal pursued by many organizations that seek success. There is awareness among organizations about the importance of studying the mental image that is formed in the minds of customers in order to be able to build plans and strategies related to improving the intellectual impressions and knowledge of customers and thus creating an appropriate environment conducive to innovation in all organization activities. The present study aims to survey the views of a sample of (89) individuals work as managers and heads of departments in the construction organizations within the city of Dohuk towards the variables of the study through the questionnaire, which was analyzed by the adoption of Statistical Package for Social Sciences (SPSS-V25). The results of the research showed that the mental image of the investigated organizations acquires most of their characteristics from the innovation value and their dimensions, and that the more the organizations investigated in the innovation value of their products, the greater positive impact on improving of the mental image of customers. The research also presented number of recommendations, such as that the researched organizations adopt a culture of creativity in dealing with the employees by enabling them to work independently and applying their innovation ideas, which reflect their positive returns on both the innovation value and mental image of those organizations.